2017
DOI: 10.1177/1073110517703102
|View full text |Cite
|
Sign up to set email alerts
|

Informed Consent in Dentistry

Abstract: A review of literature regarding informed consent in dentistry reveals a paucity of information and minimal scholarship devoted to this subject. But this begs the question about informed consent somehow being different for dentistry than for medicine or other healthcare delivery. My account draws distinctions where appropriate but is rooted in the premise that informed consent is an ethical construct applicable to vulnerable people as patients independent of what type of treatment or body part being considered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 40 publications
0
10
0
1
Order By: Relevance
“…14 Dental patients are required to read and sign informed consent forms before any dental treatment can be performed. 16 For a consent to be valid, the following conditions apply: "(1) patient competence (legal ability and capacity to understand and decide), (2) disclosure of material information (in this case by the dentist), (3) understanding (by the patient), (4) voluntariness (with respect to the patient), and ( 5) consent (patient authorization to proceed)." (page 78) 16 A number of studies have reported that dental informed consent forms fail to comply with those aims.…”
Section: Statement Of Clinical Relevancementioning
confidence: 99%
See 1 more Smart Citation
“…14 Dental patients are required to read and sign informed consent forms before any dental treatment can be performed. 16 For a consent to be valid, the following conditions apply: "(1) patient competence (legal ability and capacity to understand and decide), (2) disclosure of material information (in this case by the dentist), (3) understanding (by the patient), (4) voluntariness (with respect to the patient), and ( 5) consent (patient authorization to proceed)." (page 78) 16 A number of studies have reported that dental informed consent forms fail to comply with those aims.…”
Section: Statement Of Clinical Relevancementioning
confidence: 99%
“…16 For a consent to be valid, the following conditions apply: "(1) patient competence (legal ability and capacity to understand and decide), (2) disclosure of material information (in this case by the dentist), (3) understanding (by the patient), (4) voluntariness (with respect to the patient), and ( 5) consent (patient authorization to proceed)." (page 78) 16 A number of studies have reported that dental informed consent forms fail to comply with those aims. 17,18 Geist reported that some dental x-ray informed consent forms incorrectly stated that the American Dental Association (ADA) recommended "full-mouth series every 3 to 5 years and bitewings every 1 to 2 years."…”
Section: Statement Of Clinical Relevancementioning
confidence: 99%
“…In dentistry, obtaining informed consent from patients was introduced in the mid-1980s, and since then, this process shifted from a paternalistic-focused model to a patient autonomy-focused model [3]. Nowadays, informed consent plays an integral part in routine dental practice, which allows patients to raise concerns at any point about their treatment options [4].…”
Section: History Of Informed Consentmentioning
confidence: 99%
“…The informed consent begins with providing high quality information and employing decision‐making aids as needed, and it takes shape in three different forms : (1) Implied consent which does not need to be documented in the clinical record because it is based on the patient's passive cooperation without discussion or formal consent. However, enough information needs to be provided by the health care provider to the patient.…”
Section: Informed Consent and The Sdm Processmentioning
confidence: 99%